1994
DOI: 10.1002/bjs.1800810124
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing Nissen fundoplication and the Angelchik prosthesis

Abstract: Sixty-one patients with gastro-oesophageal reflux refractory to medical therapy were entered into a prospective randomized trial comparing the Rossetti-Hell modification of the Nissen fundoplication (n = 31) with the Angelchik prosthesis (n = 30). Mean age, sex ratio, duration of symptoms, preoperative pH profiles and manometric findings were similar in the two groups. At a mean of 84 (range 64-105) months after closure of the trial 47 patients were available for review, eight had died from unrelated causes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Five prospective studies investigate the Nissen, Hill, and Watson procedures [1-3, 11, 38]. Finally there are eight prospective randomized studies that compare the Nissen procedure with a second (2× Angelchik [17,33], 3× Toupet [22,23,34], 1× Lind [37]) or with two further operative techniques (1× Belsey and Hill [8], 1 × Toupet and LortatJacob [16]). The results of these comparative studies do not allow for a general recommendation on the individual procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five prospective studies investigate the Nissen, Hill, and Watson procedures [1-3, 11, 38]. Finally there are eight prospective randomized studies that compare the Nissen procedure with a second (2× Angelchik [17,33], 3× Toupet [22,23,34], 1× Lind [37]) or with two further operative techniques (1× Belsey and Hill [8], 1 × Toupet and LortatJacob [16]). The results of these comparative studies do not allow for a general recommendation on the individual procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these comparative studies do not allow for a general recommendation on the individual procedures. Three studies report on advantages in applying the Nissen fundoplication [16,17,33], two studies rather favor the Toupet technique [22,34], and three studies see no differences in the compared techniques [8,23,37].…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported a reoperation rate of 5-15%, with dysphagia also representing the most common reason for Angelchik removal [5, 7-9, 15, 16]. Five prospective randomized trials comparing the Angelchik ring with Nissen fundoplication [6][7][8][9]16] indicated that the Angelchik prosthesis relieves GERD symptoms as well as the Nissen procedure in the early postoperative period. However, several investigators believe that, unlike Nissen fundoplication, the incidence of dysphagia increases over time in patients with the Angelchik ring, most likely due to the formation of dense fibrous pseudocapsules around the silicone prostheses [4,13,17].…”
Section: Discussionmentioning
confidence: 96%
“…Although several studies have suggested that the Angelchik ring provides early postoperative control of GERD symptoms as well as the Nissen fundoplication (NF), reoperation for removal of Angelchik rings due to dysphagia has been necessary in 5-15% of patients [5][6][7][8][9]16]. Furthermore, the Angelchik prosthetic ring has been associated with other complications, including migration into the mediastinum and distant sites within the peritoneal cavity, as well as erosion into the gastrointestinal tract.…”
mentioning
confidence: 99%
“…Good overall long-term outcomes have been reported following open surgery [9][10][11]. DeMeester et al [9] reported a 91% success rate for Nissen fundoplication at average follow-up of 45 months.…”
mentioning
confidence: 90%